Access and allocation in earth system governance: Water and climate change compared - Gupta J. (2017)
A significant percentage of the global population does not yet have access to safe drinking water, sufficient food or energy to live in dignity. There is a continuous struggle to allocate the earth's resources among users and uses. This article argues that distributional problems have two faces: access to basic resources or ecospace; and, the allocation of environmental resources, risks, burdens, and responsibilities for causing problems. Furthermore, addressing problems of access and allocation often requires access to social processes (science, movements and law). Analysts, however, have tended to take a narrow, disciplinary approach although an integrated conceptual approach may yield better answers. This article proposes a multi-disciplinary perspective to the problem of access and allocation and illustrates its application to water management and climate change. © The Author(s) 2010.